The leadership style in educational settings A field study on a sample of middle school teachers in Tamanrasset - hambaza, chaibi; Serraya, Elhaadi (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
This study, entitled leadership style in educational settings A field study on a sample of middle school teachers in Tamanrasset to reveal the quality of the prevailing (democratic - or democratic - liberated) leadership pattern in educational institutions, and this is according to the opinion of middle education teachers in Tamanrasset, and this is evident through the leader's practice. The average manager for a specific behavior called the pattern, which he uses as a model in his dealings with his subordinates, who are professors of intermediate education, and the pattern is the characteristics of an individual, group, or culture that distinguish it from the model of an individual, group, or other culture, and this study also aims to reveal the differences in the degree of the leadership style attributed for intermediate variables (gender - seniority). The study sample consisted of 50 professors, who were chosen as a stratified random sample of intermediate education professors in Tamanrasset. We followed the descriptive method for its relevance to the type of study that describes the methods and methods of dealing within educational educational institutions between the director and the professors, and the study tool was applied, which is a form containing a set of questions that talk about leadership style and a way of dealing between the president and we mean the director and subordinates and we mean professors. And to verify the validity and consistency of the exploratory study, and the statistical treatment of the results was carried out using the SPSS statistical program to verify the validity of the hypotheses from which the research was launched, and the study reached the following results: - The prevailing leadership style in educational educational institutions is the democratic style. - There are statistically significant differences in the type of leadership style due to the gender variable. - There are statistically significant differences in the type of leadership style due to the seniority variable.